Landscape complexity promotes hoverflies across different types of semi‐natural habitats in farmland. Issue 4 (14th February 2018) - Schirmel, Jens; Albrecht, Matthias; Bauer, Philipp‐Martin; Sutter, Louis; Pfister, Sonja C.; Entling, Martin H.
Abstract: Semi‐natural habitats (SNH) provide essential resources for many organisms in agricultural landscapes and can increase biodiversity at the local and landscape scale. For the management of ecosystem services, it is crucial to understand how local characteristics of SNH and the surrounding landscape complexity affect beneficial species. We investigated this for hoverflies (Diptera: Syrphidae)—an important functional group providing both pest control and pollination services—in a total of 138 SNH within 35 agricultural landscapes in Switzerland and Germany. SNH differed in type (woody, herbaceous), shape (areal, linear) and availability of food resources (floral resources and aphids). They were located along a gradient of landscape complexity (1%–75% SNH in a 1 km radius). In total, 9, 030 hoverflies belonging to 89 species were collected. In both countries, hoverfly community composition was mainly driven by SNH type and SNH shape, in addition to landscape complexity in Switzerland. Species richness of hoverflies increased with additional SNH at the landscape scale. However, the ubiquitous and dominant aphidophagous species Episyrphus balteatus was indifferent to landscape composition. Species richness of total and aphidophagous hoverflies was higher in woody than in herbaceous SNH. Hoverfly species richness was similar in linear and areal SNH, but non‐aphidophagous hoverflies were more vulnerable to landscape simplification in linear than areal SNH. Effects of the SNH type partly differed between the two countries. In Germany, the dominant aphidophagous species E. balteatus preferred woody over herbaceous SNH, while no such difference was found in Switzerland. Overall, local richness and abundance of floral resources were poor predictors for hoverfly abundance, richness or community composition. Synthesis and applications . Hoverfly species richness and community composition in semi‐natural habitats (SNH) were mainly driven by the SNH type and landscape complexity. Conservation and restoration of complex agricultural landscapes with a high proportion of different SNH types is therefore key for the conservation of hoverfly diversity, and thus likely to promote pest control and pollination services provided by them. Thereby, local improvement of SNH to promote hoverflies has to consider regional differences in habitat characteristics. Abstract : Hoverfly species richness and community composition in semi‐natural habitats (SNH) were mainly driven by the SNH type and landscape complexity. Conservation and restoration of complex agricultural landscapes with a high proportion of different SNH types is therefore key for the conservation of hoverfly diversity, and thus likely to promote pest control and pollination services provided by them. Thereby, local improvement of SNH to promote hoverflies has to consider regional differences in habitat characteristics.